Een fenomenologie van de openbaring: Hedendaagse ontmoetingen met de heilige Ignatius van Loyola - Horner, Robyn ca. 20./21. Jh. (Tijdschrift voor theologie, 2018)
In an academic context, to speak of revelation is frequently to exclude oneself immediately from the possibility of serious philosophical or other conversation. And in many Western cultural contexts, the idea of belief in God on the basis of revelation is often greeted with sheer incredulity. It is my view that the sense that revelation is an incoherent or outmoded concept relates in some ways to the perceived gap between revelation and experience. What is needed, then, is a way of thinking about revelation that permits credible dialogue about it to take place within contemporary thought and culture, particularly in the context of personal experience. My argument is that recent developments within French phenomenology allow for this kind of dialogue, and that Ignatius'